Analysis of Differences between INA CBG’s Rates and Hospital Real Rates in Hemophilia Patients at RSUD Zainoel Abidin Banda Aceh - Haslinur, Sari; Saputra, Irwan; Syahrizal, Dedy; Bakhtiar, Bakhtiar; Usman, Said (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
INA CBG’s rate is system of health financing packages from government based on cased and hospital services. Real tariff are the actual costs incurred by hospitals service based to local governments. During this time there are differences between INA CBGs rated and hospital rates. Hemophilia is a high-cost disease paid by INA CBGs. The aim of this study was to analyze the differences of INA CBGs and real rates in Hemophilia Patients at RSUDZA Banda Aceh. The research used quantitative analyticmethod. Data collection was carried out by taking secondary data from visits of hemophilia patients at RSUDZA in January-Desember 2019. The study population was all hemophilia patients in RSUDZA in 2019 with purpousive random sample of 100 people. There was a significant difference between INA CBGs rated and hospital rates rates in Hemophilia Patients at RSUDZA Banda Aceh.which indicated by p-value 0,000. Differences between INA CBGs and real rates of hospital are Rp.-431.095.538 or -25%. Differences of INA CBGs rated dan real rates causes’ hospital loss, but hospital needs to re-review the calculation of more efficient service cost to improve the quality of service.